Humanitarian reform and new institutional responses - Dennis McNamara (Forced Migration Review, 2006)
In 1998, in their groundbreaking book Masses inFlight, Roberta Cohen and Francis Deng noted theweakness of inter-agency coordination, lack of clearinstitutional responsibility for IDPs and unevenresponse to their needs. Has anything changed?